Sustainable Poverty Reduction in Less-Favoured Areas - Ruben, R (CABI, 2014)
Poor people living in less-favoured areas (LFAs) represent globally around 40% of the rural population suffering from chronic poverty. Given the limited agricultural potential and difficult access conditions in these areas, standard devices for enhancing rural development cannot appropriately address issues of poverty alleviation and sustainable natural resource management. Escaping from the downward spiral of poverty and resource degradation requires the identification of suitable pathways enabling rural households to develop production systems and livelihoods that respond to local conditions (Pender et al., 2001a, b; Pender, 2004; Hazell et al., 2006).